Adsorption of Alizarin Red S onto Nano-Sized Silica Modified with γ-Aminopropyltriethoxysilane - Deliang Li; Qing Liu; Shuanglong Ma; Zhixian Chang; Ling Zhang (Adsorption Science & Technology)
The adsorption of Alizarin Red S (ARS) dye onto nano-sized silica modified with γ-aminopropyltriethoxysilane (AMNS) was studied. The effects of the initial pH and concentration of the ARS solution, the AMNS dosage, the contact time and temperature on the removal and adsorption capacities have been investigated. The experimental isotherm data were analyzed using the Langmuir and Freundlich equations. The adsorption of ARS onto AMNS followed the Langmuir model, the maximum adsorption capacity being estimated as 200 mg/g. The application of three kinetic models, viz. pseudo-first-order, pseudo-second-order and intra-particle diffusion, to the experimental kinetic data was discussed. It was shown that the sorption processes were better fitted by the pseudo-second-order equation. From thermodynamic studies, the values of the Gibbs' free energy (ΔG 0 ), standard enthalpy change (ΔH 0 ) and standard entropy change (ΔS 0 ) were calculated as −3.78 kJ/mol, −90.05 kJ/mol and −289.34 J/(mol K), respectively, thereby indicating that the adsorption process was spontaneous and exothermic.